An empirical analysis of rural farmers' financing intention of inclusive finance in China: The moderating role of digital finance and social enterprise embeddedness. Issue 7 (26th June 2019) - Aisaiti, Gulizhaer; Liu, Luhao; Xie, Jiaping; Yang, Jun
Abstract : Purpose: The purpose of this paper is to investigate and understand China's rural farmers' financing intention of inclusive finance, and it examines related drivers like knowledge of inclusive finance, perceived benefits and perceived risks of ordering finance. Besides, the social enterprise embeddedness and digital finance are integrated into the conceptual model to further investigate their moderating impact. Design/methodology/approach: The authors designed an inclusive finance intention model to examine the relations between dependent variable knowledge of inclusive finance, intermediary variables perceived benefits and perceived risks of ordering finance and the independent variable financing intention of inclusive finance. The embeddedness of social enterprise and digital finance were identified as modifying factors. Both exploratory and conclusive research strategies were applied. A structured questionnaire was developed to collect empirical data from the rural areas of China. Findings: It suggests that knowledge of inclusive finance can strengthen both perceived benefits and perceived risk of ordering finance. Interestingly, the embeddness of social enterprise can significantly reduce risk perceptions and improve perceived benefits of ordering finance. Furthermore, perceived benefits of ordering finance can positively enhance rural farmers' financing intention of inclusive finance, whereas perceived risks can negatively influence the financing intention. Moreover, digital finance as a modifying factor can significantly strengthen the positive correlation between perceived benefits of ordering finance and financing intention of inclusive finance. Practical implications: The research indicates that a systematic inclusive finance educational project is needed to enhance rural farmers' understanding of inclusive finance and its components. Moreover, the study reveals that it is crucial to promote social enterprise participation and digital finance to develop inclusive finance in rural China, as the service attributes of social enterprise and efficiency of digital finance can greatly reduce the existing transaction cost of farmers. Originality/value: The conceptual model would potentially contribute to researchers interested in investigating the financing intention of inclusive financial services relating to rural population. The integration of social enterprise embeddedness and digital finance is the uniqueness of this research conceptual model.